2017
DOI: 10.14503/thij-15-5626
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Antigen 125 is Associated with Length of Stay in Patients with Acute Heart Failure

Abstract: Length of stay is the primary driver of heart-failure hospitalization costs. Because cancer antigen 125 has been associated with poor morbidity and mortality rates in heart failure, we investigated the relationship between admission cancer antigen 125 levels and lengths of stay in heart-failure patients. A total of 267 consecutive patients (184 men, 83 women) with acute decompensated heart failure were evaluated prospectively. The median length of stay was 4 days, and the patients were classified into 2 groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Kaya et al . [ 13 ] found that CA125 was associated with longer hospital stays and an increased risk of re-readmission in HF; in patients hospitalized for more than four days, CA125 values were higher (114 [9–298] U/ml) compared to patients who were hospitalized for less than four days (19 [3–68] U/ml, P < 0.001). Hung et al .…”
Section: Discussionmentioning
confidence: 99%
“…Kaya et al . [ 13 ] found that CA125 was associated with longer hospital stays and an increased risk of re-readmission in HF; in patients hospitalized for more than four days, CA125 values were higher (114 [9–298] U/ml) compared to patients who were hospitalized for less than four days (19 [3–68] U/ml, P < 0.001). Hung et al .…”
Section: Discussionmentioning
confidence: 99%